Fungal volatile fingerprints: discrimination between dermatophyte species and strains by means of an electronic nose. - Sahgal, Natasha; Magan, Naresh (Elsevier, 2008)
The potential of an electronic nose (e-nose) consisting of a hybrid gas sensor array system has been examined for species discrimination and strain identification of dermatophytes which are causative pathogens for human and animal infection. Temporal volatile production patterns have been studied at a species level for a Microsporum species, two Trichophyton species and at a strain level for the two Trichophyton species. After about 120 h principal component analysis (PCA) and cluster analysis showed possible discrimination between the species from controls. Data analysis also indicated probable differentiation between the strains of T. rubrum. The same could not however be achieved for the strains of T. mentagrophytes during preliminary experiments for the same time period, signifying a good similarity between the strains of this particular species based on their volatile fingerprints. This study suggests that volatile production patterns shows promise for species and strain identification of these dermatophytic fungi thereby facilitating early diagnosis and early management of patients.
Keywords: Dermatophytes; Electronic nose; Volatile fingerprints; Strain and species differentiation; Metal oxide sensors